Concomitant off-pump coronary artery bypass and non-cardiovascular surgery - Oh, Hong Chul; Han, Jung Wook; Choi, Jae-Woong; Kim, Yong Han; Hwang, Ho Young; Kim, Ki-Bong (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Background: Reports on concomitant cardiac and non-cardiovascular surgeries have noted disadvantages in the use of extracorporeal circulation. We assessed the results of concomitant off-pump coronary artery bypass (OPCAB) and non-cardiovascular surgery, and compared them with isolated OPCAB results. Methods: Of 2,439 patients who underwent OPCAB between 1999 and 2014, 115 patients underwent concomitant OPCAB and non-cardiovascular surgery. Combined non-cardiovascular diseases included 63 malignant and 52 benign diseases. Concomitant non-cardiovascular surgeries performed were general (n=62), thoracic (n=47), orthopedic (n=3), urologic (n=2) and otolaryngologic surgeries (n=1). Operative results were compared between the OPCAB patients who underwent concomitant non-cardiovascular surgeries (group 1, n=115) and isolated OPCAB patients (group 2, n=2,251). Because preoperative characteristics of the two groups were different, a 1:2 propensity score-matched analysis was performed and operative results of the two matched groups were compared. Results: Operative mortality rates were 0.9% (1/115) in group 1 and 1.0% (22/2,251) in group 2 (P=0.909). Although there were differences in preoperative patient characteristics, postoperative complications, including atrial fibrillation (36.5% vs. 28.8%), perioperative myocardial infarction (MI) (4.3% vs. 5.2%), acute renal failure (1.7% vs. 4.9%), mediastinitis (0.9% vs. 0.8%), bleeding reoperation (0.9% vs. 2.9%), and respiratory complications (2.6% vs. 2.1%), did not show significant differences between the two groups. After a 1:2 propensity score-matched analysis, there were no statistical differences in operative complications between the two groups. Conclusions: Concomitant OPCAB and non-cardiovascular surgeries were not associated with increased mortality and postoperative morbidities when compared with isolated OPCAB.